BUILDING STUDENT MORALITY AND ETHICS AT MA NURUL HASAN BRANI WETAN: BASIC LEARNING STRATEGY IN EFFECTIVE STUDENT CHARACTER BUILDING - Inayah, Nur; Hifdil Islam, Muhammad; Lailia Maghfiroh, Ummi (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to describe the implementation of the basic learning strategy in shaping students' morality and ethics at MA Nurul Hasan Brani Wetan, as well as to identify the obstacles encountered during its implementation. The research employed a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The findings indicate that the basic learning strategy is applied through positive habituation, teacher role modeling, integration of values into learning, and reinforcement of Islamic-themed extracurricular activities. This strategy has proven effective in significantly enhancing students' moral and ethical awareness. However, its implementation still faces challenges, such as the lack of parental involvement, the negative influence of social media, and limited teacher capacity in managing character education. The study recommends the need for synergy between schools, families, and communities, as well as regular teacher training to optimize the implementation of value-based character development strategies.